Encyclopedia of food and culture. Volume 2, Food production to Nuts - Katz, Solomon H., 1939-; Weaver, William Woys, 1947- (Detroit : Thomson/Gale, 2003)
Contains over 150 entries that provide information about the essential aspects of food, its history, and its cultural diversity, including articles on people who have been influential in food history. Arranged alphabetically from food production-to-nuts, with maps, illustrations, and sidebars.
Includes bibliographical references.
Young Adult
Keywords: Food habits -- Encyclopedias; Food -- Encyclopedias; Eating customs -- Encyclopedias; Food -- Encyclopedias